2020
DOI: 10.1016/j.scitotenv.2020.138820
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic and environmental pollution: A blessing in disguise?

Abstract: In late 2019, a novel infectious disease with human to human transmission was identified in Wuhan China, which now has turned into a global pandemic. Countries all over the world has implemented some sort of lockdown to slow down its infection and mitigate it.Lockdown due to COVID-19 has drastic effects on social and economic fronts. However, this lockdown also have some positive effect on natural environment. Recent data released by NASA (National Aeronautics and Space Administration) and ESA (European Space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
772
2
29

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 896 publications
(843 citation statements)
references
References 8 publications
40
772
2
29
Order By: Relevance
“…In another study, Şahin (2020) analysed the impact of weather parameter on COVID-19 in Turkey. Association between COVID-19 and climate indicators was also demonstrated by Muhammad et. al., (2020) in New York, USA.…”
Section: Introductionsupporting
confidence: 70%
“…In another study, Şahin (2020) analysed the impact of weather parameter on COVID-19 in Turkey. Association between COVID-19 and climate indicators was also demonstrated by Muhammad et. al., (2020) in New York, USA.…”
Section: Introductionsupporting
confidence: 70%
“…Recent results over the last few years have reported results from global to molecular scales an increased understanding of bio aerosol and its health effects (Humbal et al 2020;Humbal et al 2018). However, further research is required to understand the open questions based on interdisciplinary and complex nature of aerosol with respect the relationship with human health (Kagaya et al 2020;Muhammad et al 2020).…”
mentioning
confidence: 99%
“…In these circumstances, a worldwide reduction of pollution has been observed, especially in urban areas. An estimation found that the public mobility is reduced by 90% due to the pandemic that results a reduction of pollution by almost 30% in the epicenters of the disease like Wuhan, Italy, Spain, and the USA (Muhammad et al 2020). Similar air pollution reduction results have also been found in the neighboring country's capital city, viz.…”
Section: Introductionmentioning
confidence: 58%
“…For example, the concentration of NO, NO 2 , and CO has been reduced by up to 77, 54, and 65%, respectively, in Sao Paulo, Brazil (Nakada and Urban 2020). Furthermore, Muhammad et al (2020) found that the concentration of NO 2 has decreased by up to 20-30% in China, Spain, France, Italy, and the USA, which are major epicenters of COVID-19. In compare to Delhi and Sao Paulo, Dhaka has also experienced the reduction of PM 2.5 , NO 2 , CO, and AQI but the extent or magnitude of the reduction is less than these two cities (23% for PM 2.5 , 30% for NO 2 , 07% for CO, and about 35% for AQI on average).…”
Section: Discussionmentioning
confidence: 99%